Biochemical Profile, Biological Activities, and Toxic Effects of Proteins in the Rhinella schneideri Parotoid Gland Secretion. Issue 8 (31st August 2016) - Sousa‐Filho, Luis M.; Freitas, Cleverson D. T.; Lobo, Marina D. P.; Monteiro‐Moreira, Ana C. O.; Silva, Renan O.; Santana, Lucas A. B.; Ribeiro, Ronaldo A.; Souza, Marcellus H. L. P.; Ferreira, Gustavo P.; Pereira, Anna C. T. C.; Barbosa, André L. R.; Lima, Mauro S. C. S.; et al.
ABSTRACT: Parotoid glands of amphibians are known for the production of several biologically active compounds having pharmacological and toxic effects in mammals. In the present work, a protein fraction obtained from Rhinella schneideri parotoid gland (RsPP) was characterized to study its biological and toxic effects. Rhinella schneideri parotoid secretion is composed of up to 30% (w/w) of soluble proteins. Tandem mass spectrometric analysis of the RsPP identified 104 proteins, including actin, beta‐actin, ribosomal proteins, catalase, galectin, and uncharacterized proteins; however, no peptidases were found, and this result was reinforced by the absence of proteolytic activity. In addition, RsPP did not exhibit pro‐coagulant or antibacterial effects. However, pretreatment of mice with different doses of RsPP intraperitoneally inhibited carrageenan‐induced paw edema and increased tissue myeloperoxidase activity. RsPP also reduced interleukin 1β levels in the peritoneal cavities and cell migration in the peritoneal cavities of an animal model of carrageenan‐induced peritonitis. Subchronic treatment of animals with RsPP for 7 consecutive days did not alter the serum biochemical, renal, or liver parameters. However, a significant reduction in blood leukocyte count was observed. Our results showed that R. schneideri parotoid secretion contains proteins with anti‐inflammatory and slight toxic effects.